Intelectual Capital, Green Accounting, And Company Performance With The Manufacturing Company - Nuraini (UNIB Press, 2023)
This study aims to determine the application of Intelectual Capital green accounting, and company performance with the Manufacturing Company . This research uses quantitative research. The population in this study are mining companies listed on the Manufacturing Company for 2021-2023. The sampling technique used in this study used purposive sampling . The number of companies sampled in this study were 40 companies. The type of data used is secondary data, namely in the form of financial reports and annual reports obtained through the official website of the Indonesia Stock Exchange and the official websites of related companies. The dependent variable used in this study is Company Performance. Meanwhile, the independent variables use intelectual capital and green accounting. The data analysis method used is panel data regression analysis with the help of the SPSS application program. The results of this study indicate that intelectual Capital and green accounting have a positive and significant effect on company performance.